Menaggio, Italien. Das Gerichtswesen der Römischen Kaiserzeit. Drei trinationale Forschungskonferenzen an der Villa Vigoni - Haensch, Rudolf (e-Forschungsberichte des DAI, 2023)
In front of the Justice and on the See, we are in the hands of God: The legal system of the imperial era in the light of the documentary evidences. ‒ Three tri-national conferences in the Villa Vigoni.